2000
DOI: 10.1152/ajpheart.2000.279.3.h1239
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of baroreflex vagal bradycardia by activation of the rostral ventrolateral medulla in rats

Abstract: In stressful conditions, baroreflex vagal bradycardia (BVB) is often suppressed while blood pressure is increased. To address the role of the rostral ventrolateral medulla (RVL), a principal source of sympathetic tone, in inhibition of BVB, we microinjected DL-homocysteic acid (DLH, 6 nmol) into the RVL of chloralose-urethan-anesthetized, sinoaortic-denervated rats to examine the effect on BVB. The BVB was provoked by electrical stimulation of the aortic depressor nerve ipsilateral to the injection sites. DLH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…We observed that hypotension induced by the chip system was accompanied by significant bradycardia, which was caused by increased afferent activity of the ADN, and subsequent inhibition of sympathetic nerves and excitation of vagi (Cravo and Morrison, 1993;Aicher et al, 2000;Nosaka et al, 2000). The present study showed that the treatment with either methyl atropine or vagotomy blocked the bradycardia completely but produced no significant effect on hypotension induced by the chip system compared with the control group, and that MAP could still be satisfactorily maintained in the artificial set point level.…”
Section: Discussioncontrasting
confidence: 43%
“…We observed that hypotension induced by the chip system was accompanied by significant bradycardia, which was caused by increased afferent activity of the ADN, and subsequent inhibition of sympathetic nerves and excitation of vagi (Cravo and Morrison, 1993;Aicher et al, 2000;Nosaka et al, 2000). The present study showed that the treatment with either methyl atropine or vagotomy blocked the bradycardia completely but produced no significant effect on hypotension induced by the chip system compared with the control group, and that MAP could still be satisfactorily maintained in the artificial set point level.…”
Section: Discussioncontrasting
confidence: 43%
“…Stimulation of presynaptic ␣-2 adrenoceptors may modulate acetylcholine release from cholinergic neurons innervating the heart. 32 Remarkably, clonidine changed the relationship between systolic BP changes and cardiac stroke volume. With placebo, stroke volume increased as RR interval increased.…”
Section: Tank Et Al ␣-2 Adrenoceptors and Baroreflex In Humansmentioning
confidence: 98%
“…31 Decreased activity in this area may lead to a secondary increase in parasympathetic activity. 32 It is also possible that clonidine directly influences other areas in the brain stem like vagal nuclei or the caudal ventrolateral medulla. Indeed, ␣-2 adrenoreceptors are highly expressed in vagus motor nuclei in animals and in humans.…”
Section: Tank Et Al ␣-2 Adrenoceptors and Baroreflex In Humansmentioning
confidence: 99%
“…The early bradycardia could be a baroreflex-mediated attempt to counteract the rapidly rising blood pressure. Within 2 min, this vagal activation is reversed into vagal inhibition, either by rapid resetting of baroreceptors (Dorward and Korner, 1987;Hatton et al, 1997) or centrally mediated mechanisms overriding the baroreflex (Djojosugito et al, 1970;Nosaka et al, 2000). In methylatropine-treated rats, these changes in vagal activity are blocked, leading to a very rapid increase in heart rate (no vagal activation to counteract the tachycardia) to a plateau significantly below that found in saline-treated controls (no vagal inhibition).…”
mentioning
confidence: 99%